Chinese and Annamese ceramics - Joseph, Adrian (Aldrian Malcom) ([Hugh Moss (Publishing) Ltd.], 1973)
The Chinese Wares: The custom of burying objects with the dead is one that has been practised by mankind for thousand years. The two main reasons for this were to provide for the after-life and to give reassurance to the departed in the spirit world by virtue of familiar surroundings. The ritual has thus provided us with a great deal of valuable information about the people concerned and their way of life. Sometimes the information extends beyond the domestic scene and concerns the trade and social intercourse of the period. Such has been the case in the Philippines and Indonesia, where the ritual of burying objects with the dead was observed from prehistoric times until the coming of the Spaniards during the sixteenth century. -- The Annamese Wares: The ceramic wares of the Annam are in many ways as exciting as those of China itself. The name Annam has from time to time been used to designated various areas of what is today Vietnam, but we are referring here to that part which occupies an area of some 30,000 square miles with Hanoi, the capital, as its centre. The name is the one that has been used by the Chinese for this territory and it means 'pacified South'.